Case Report: An unexpected diagnosis of cutaneous Mycobacterium marinum infection based on potato dextrose agar culture - Xia, Xiujiao; Li, Jiajia; Liu, Zehu (Frontiers in Medicine, 2025)
Non-tuberculous mycobacteria (NTM) are slender, non-motile, acid-fast bacilli widely distributed in diverse environmental reservoirs across the globe. In recent years, the incidence of NTM-related diseases has risen significantly, leading to their recognition as major emerging human pathogens. Cutaneous NTM infections typically arise following traumatic injury, surgical intervention, or cosmetic procedures. Due to their heterogeneous clinical presentations, these infections often pose diagnostic challenges. Löwenstein-Jensen medium and Middlebrook medium are widely employed in mycobacterial microbiology and are capable of supporting the growth of most NTM. However, their high cost and limited availability pose significant challenges for implementation in resource-limited settings (RLS). Previously, we successfully isolated a strain of Mycobacterium marinum from a clinical sample using potato dextrose agar (PDA) medium. This finding suggests that PDA may be applicable for the primary culture of NTM, particularly M. marinum. For RLS, this medium could represent a beneficial alternative to traditional mycobacterial culture media.